Prevalence of various removable functional appliances - an institutional set up - REDDY J, MEGHANA; RENGALAKSHMI, SRI; RAJENDRAN, DEEPIKA (The journal of contemporary issues in business and government, 2021)
Orthodontic treatment is aimed at improving facial and dental appearances as well as enhancing the relationships of the teeth and skeletal bases to each other.The goal of early treatment is to correct existing or developing skeletal, dentoalveolar and muscular imbalances.Class II malocclusion is one of the most common orthodontic problems.There are a number of modalities available for managing Class II malocclusions. Some of the more common options include extraoral traction appliances, arch expansion appliances, extraction procedures, functional jaw orthopaedic appliances and orthognathic surgery. The most commonly used removable functional appliances are activator, frankel and twin block. The Aim of the study is to find out the prevalence of various removable functional appliances used in SDC. A University- based study was conducted among 32 patients with removable functional appliances in the age group of 5 to 40 years from June 2019 to March 2020. Data collection was done by reviewing the patient records and analysing the data of 32 patients, the Variables collected included the age, gender and the type of removable functional appliance used. The data was entered into Excel tabulation was done, statistical analysis was done using SPSS and Pearson chi-square test. Total 32 patients undergoing removable functional therapy were chosen out of which 14 were females and 18 were males.Twin block was found to be the most prevalent appliance with 62.5% followed by activator (15.63%), frankel (9.38%) and other appliances were 12.5%. Within the limits of this Study, it was concluded that the twin block is the most commonly used removable functional appliance.